A novel form of ficin from Ficus carica latex: Purification and characterization. (September 2015) - Baeyens-Volant, Danielle; Matagne, André; El Mahyaoui, Rachida; Wattiez, Ruddy; Azarkan, Mohamed
Graphical abstract: A novel ficin form was isolated from Ficus carica latex by combination of cation-exchange, hydrophobic interaction, affinity and fplc-gel filtration chromatographies. Mass spectrometry and far-UV CD analyses revealed very close molecular mass and secondary structure contents comparable to the known ficins. N-terminal sequencing and gel electrophoresis clearly demonstrated a novel protease form. Enzymatic activity measurements suggested different substrate specificities. The novel ficin resembles a papain-like protease according to inhibitory activity data. Highlights: A ficin was purified from Ficus carica latex. It is a novel form according to mass spectrometry and electrophoretic mobility. It is a papain-like protease according to inhibitory activity data. It showed similar secondary and 3D structures to papain-like proteases. The novel ficin was not prone to thiol pegylation, allowing its purification. Abstract: A novel ficin form, named ficin E, was purified from fig tree latex by a combination of cation-exchange chromatography on SP-Sepharose Fast Flow, Thiopropyl Sepharose 4B and fplc-gel filtration chromatography. The new ficin appeared not to be sensitive to thiol derivatization by a polyethylene glycol derivative, allowing its purification. The protease is homogeneous according to PAGE, SDS–PAGE, mass spectrometry, N-terminal micro-sequencing analyses and E-64 active site titration. N-terminal sequencing of the first ten residues has shown high identity with the other known ficin (iso)forms. The molecular weight was found to be (24, 294 ± 10) Da by mass spectrometry, a lower value than the apparent molecular weight observed on SDS–PAGE, around 27 kDa. Far-UV CD data revealed a secondary structure content of 22% α-helix and 26% β-sheet. The protein is not glycosylated as shown by carbohydrate analysis. pH and temperature measurements indicated maxima activity at pH 6.0 and 50 °C, respectively. Preliminary pH stability analyses have shown that the protease conserved its compact structure in slightly acidic, neutral and alkaline media but at acidic pH (<3), the formation of some relaxed or molten state was evidenced by 8-anilino-1-naphtalenesulfonic acid binding characteristics. Comparison with the known ficins A, B, C, D1 and D2 (iso)forms revealed that ficin E showed activity profile that looked like ficin A against two chromogenic substrates while it resembled ficins D1 and D2 against three fluorogenic substrates. Enzymatic activity of ficin E was not affected by Mg 2+, Ca 2+ and Mn 2+ at a concentration up to 10 mM. However, the activity was completely suppressed by Zn 2+ at a concentration of 1 mM. Inhibitory activity measurements clearly identified the enzyme as a cysteine protease, being unaffected by synthetic (Pefabloc SC, benzamidine) and by natural proteinaceous (aprotinin) serine proteases inhibitors, by aspartic proteases inhibitors (pepstatin A) and by metallo-proteases inhibitors (EDTA, EGTA). Surprisingly, it was well affected by the metallo-protease inhibitor o-phenanthroline. The enzymatic activity was however completely blocked by cysteine proteases inhibitors (E-64, iodoacetamide), by thiol-blocking compounds (HgCl2 ) and by cysteine/serine proteases inhibitors (TLCK and TPCK). This is a novel ficin form according to peptide mass fingerprint analysis, specific amidase activity, SDS–PAGE and PAGE electrophoretic mobility, N-terminal sequencing and unproneness to thiol pegylation.